The ATP-Gated P2X7 Receptor As a Target for the Treatment of Drug-Resistant Epilepsy - Beamer, Edward; Fischer, Wolfgang; Engel, Tobias (Frontiers in Neuroscience, 2017)
Despite the progress made in the development of new antiepileptic drugs (AEDs), the biggest challenges that epilepsy presents to drug development have remained unchanged for the last 80 years: finding a treatment with potential for modifying disease progression and reducing the percentage of patients resistant to all pharmacological interventions. The mechanism of action of the majority of AEDs is based on blocking Na+ and/or Ca2+ channels, promotion of GABA or inhibition of glutamate signalling. In order for further progress to be made, however, a fuller picture of epilepsy will need to be considered, including changes to blood-brain barrier permeability, synaptic plasticity, network reorganization and gliosis. In particular, brain inflammation has attracted much attention over recent years. Emerging evidence demonstrates a causal role for brain inflammation in lowering seizure thresholds and driving epileptogenesis. Consistent with this, intervening in pro-inflammatory cascades has shown promise in animal models of epilepsy, with clinical trials of anti-inflammatory agents already underway. The ATP-gated purinergic P2X7 receptor (P2X7) has been proposed as a novel drug target for a host of neurological conditions, including epilepsy. Constitutive expression of P2X7 in the CNS is mainly on microglia, but neuronal and astroglial expression has also been suggested. Its function as a gatekeeper of inflammation is most clearly understood, however, it also plays a number of other important roles pertinent to icto- and epileptogenesis: depolarization of the cell membrane, release of macromolecules, induction of apoptosis and synaptic reorganization. Changes in P2X7 expression have been reported following prolonged seizures (status epilepticus) and during chronic epilepsy in both experimental models and patients. While much of the early work focused on the study of P2X7 during status epilepticus, there is now mounting data showing involvement of this receptor during epilepsy. The present short review will discuss the most recent findings concerning P2X7 expression and function during epilepsy and the clinical potential for P2X7 antagonists as novel antiepileptic drugs.